MHD stagnation point flow with suction towards a shrinking sheet - Lok, Yian Yian; Anuar Ishak,; Ioan Pop, (Universiti Kebangsaan Malaysia, 2011)
A steady two-dimensional magnetohydrodynamic (MHD) stagnation-point flow of a viscous and electrically conducting fluid over a permeable shrinking sheet has been studied. The governing partial differential equations are reduced to the nonlinear ordinary differential equations by a similarity transformation. The resulting differential equations are then solved numerically using an implicit finite difference method. It is found that the solutions are non-unique for weak magnetic field, strong suction and large velocity ratio between free stream velocity and wall shrinking velocity.